Does active labour market policy affect structural unemployment? An empirical investigation for West German regions, 1986 to 1993 - Thiess Büttner; Hedwig Prey (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1997)
In this paper, the impact of two instruments of active labor market policy (ALMP), namely continuous training programs and job creation schemes, on structural unemployment in West Germany for the period 1986 to 1993 is estimated using data for 74 planning regions. Based on a disequilibrium approach, we focus on a possible effect of ALMP programs on the labor market mismatch. Taking care of endogeneity, we do not find an effect of training programs on the mismatch. For job-creation schemes, the estimates reveal positive effects on the matching-efficiency, indicating that they contributed to a reduction in the structural rate of unemployment in West Germany during the time period considered.
Keywords: 330; evaluation; active labor market policy; labor market mismatch; West Germany